2018
DOI: 10.1192/bjo.2017.2
|View full text |Cite|
|
Sign up to set email alerts
|

A symptom-based approach to treatment of psychosis in autism spectrum disorder

Abstract: SummaryThe optimal management of autism with psychosis remains unclear. This report describes a 22-year-old man with autism and psychosis who was referred to a tertiary-level specialist psychosis service, following a 6-year history of deterioration in mental health starting around the time of sitting GCSE examinations and an episode of bullying at school. We describe the individualised symptom-based approach that was effective in his treatment.Declaration of interestThe authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Clinical monitoring enabled the proper detection and management of these effects without severe consequences. Seven patients (5.7%) discontinued treatment due to adverse effects (Beebani et al, 2022; Bell et al, 2018; Estay et al, 2018; Grubisha et al, 2014; Scala et al, 2023; Skarpathiotakis and Westreich, 2005; Watchel et al, 2015 ) . Scala et al (2023) and Bell et al (2018) reported cases where clozapine exacerbated obsessive-compulsive symptoms despite alleviating psychiatric symptoms, leading to treatment interruption.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical monitoring enabled the proper detection and management of these effects without severe consequences. Seven patients (5.7%) discontinued treatment due to adverse effects (Beebani et al, 2022; Bell et al, 2018; Estay et al, 2018; Grubisha et al, 2014; Scala et al, 2023; Skarpathiotakis and Westreich, 2005; Watchel et al, 2015 ) . Scala et al (2023) and Bell et al (2018) reported cases where clozapine exacerbated obsessive-compulsive symptoms despite alleviating psychiatric symptoms, leading to treatment interruption.…”
Section: Resultsmentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD), defined by the Diagnostic and Treatment Manual for Mental Disorders, Fifth Edition (DSM-5), is characterized by persistent deficits in social communication interaction and restricted-repetitive patterns of behavior, interests or activities. A specific subtype of ASD is linked to comorbid psychosis, showing positive symptoms of delusion, hallucination, thought disorder, mania and depression and negative symptoms of psychosis appear to share many features with ASD [177]. Cognitive deficits including mental deterioration, are associated with social and communication difficulties that involve components of cognition, communication and social understanding [178].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD), defined by the Diagnostic and Treatment Manual for Mental Disorders, Fifth Edition (DSM-5), is characterized by persistent deficits in social communication interaction and restricted-repetitive patterns of behavior, interests, or activities. A specific subtype of ASD is linked to comorbid psychosis, showing positive symptoms of delusion, hallucination, thought disorder, mania and depression and negative symptoms of psychosis appear to share many features with ASD [176]. Cognitive deficits including mental retardation, are associated with social and communication difficulties that involve components of cognition, communication, and social understanding [177].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%